THE PROBLEM OF STATIN USE IN PATIENTS WITH CARDIOVASCULAR DISEASES AND CONCOMITANT LIVER DISEASES. WHAT PREVENTS OVERCOMING STATINOPHOBIA? - S. N. Bel'diev (Столичная издательская компания, 2016)
According to a recent study, Russian physicians often and sometimes unreasonably find it impossible to use statins in patients with cardiovascular diseases and concomitant chronic liver diseases. Analysis of domestic publications of recent years reveals the following factors which can impede overcoming statinophobia: 1) fragmentary and contradictory statement of the problem "Statins and liver" in Russian clinical guidelines for management of patients with high cardiovascular risk; 2) common perception that isolated transaminase increase in response to statin therapy is an indicator of "cytolysis" or "cytolytic syndrome"; 3) unreasonably overestimated lipid-lowering activity of combination therapy with low doses of statins and ursodeoxycholic acid; 4) view of the inadmissibility of statin use in patients with transaminase levels more than three upper limit of normal. To overcome these shortcomings and mistakes it seems appropriate to issue national clinical guidelines on statin use in high cardiovascular risk patients with underlying liver disease and/or with elevated transaminases.